The Challenge of Adult Re-Entry to Education: A Study in Likasi City - Dongangaokar, Pradnya; Joshi, Saumya; Khetan, Aanchal; Kumar, Sushil (Journal of Research in Vocational Education, 2025)
The objective of this work is to show the reasons that push people of advanced age to return to school to strengthen or broaden their scientific skills. This work also shows the difficulties that adults face when they return to school.